2015
DOI: 10.1515/opli-2015-0001
|View full text |Cite
|
Sign up to set email alerts
|

Other-initiated repair in Siwu

Abstract: This article describes the interactional patterns and linguistic structures associated with other-initiated repair in Siwu, a Kwa language spoken in eastern Ghana. Other-initiated repair is the set of techniques used by people to deal with problems in speaking, hearing and understanding. Formats for repair initiation in Siwu exploit language-specific resources like question words and noun class morphology. At the same time, the basic structure of the system bears a strong similarity to other-initiated repair i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
3
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(15 citation statements)
references
References 20 publications
1
14
0
Order By: Relevance
“…The freezelook refers to when a speaker briefly "freezes" their posture while fixing their gaze on their interlocutor, which is particularly salient when the person providing the freeze-look was expected to provide a response to an interlocutor's question. This phenomenon, which has been described both for spoken [54,55] as well as signed languages [55,56], may thus provide a visual signal through a lack of movement.…”
Section: Discussionmentioning
confidence: 89%
“…The freezelook refers to when a speaker briefly "freezes" their posture while fixing their gaze on their interlocutor, which is particularly salient when the person providing the freeze-look was expected to provide a response to an interlocutor's question. This phenomenon, which has been described both for spoken [54,55] as well as signed languages [55,56], may thus provide a visual signal through a lack of movement.…”
Section: Discussionmentioning
confidence: 89%
“…A few studies provide initial clues that eyebrow movements may not be epiphenomenal in spoken OIR (36)(37)(38). Comparing OIR sequences in unrelated spoken-and signed languages (Northern Italian, Cha'palaa, Argentine Sign Language), Floyd and colleagues (38) showed that if a repair initiation was accompanied by a bodily "hold", that is, if body movements like eyebrow movements (but also, e.g., hand gestures or head movements) were "temporarily and meaningfully held static" (ibid., p. 1), this hold was often associated with communication problems and not disengaged from until the communication problem was solved.…”
Section: Study 1 Eyebrow Movements As Signals Of Communicative Proble...mentioning
confidence: 99%
“…Note that Floyd et al (38) did not distinguish between different types of brow movements such as furrows versus raises, though. Furthermore, two individual descriptive examples-one from English ("raises her eyebrows, pulls down the corner of the mouth"; (37), p. 11) and one from Siwu ("puzzled look: furrowing of eyebrows", (36), p. 238)-suggest that facial signals including eyebrow raises or furrows can be treated as repair initiations without relying on accompanying verbal material. While these studies suggest that eyebrow movements may serve a communicative role in initiating repair both in signed as well as spoken language, more systematic evidence for spoken language is needed.…”
Section: Study 1 Eyebrow Movements As Signals Of Communicative Proble...mentioning
confidence: 99%
“…The method was pioneered by Michael Moerman (1977, 1988, 1993) in his analysis of conversational Thai data. Among the practitioners of this methodological approach are Charles Goodwin (1980), Marjorie Goodwin (1990), Charles Goodwin and Marjorie Goodwin (1987, 1992), Sidnell (2001, 2005, 2007, 2008) and linguists affiliated with the Max Planck Institute for Psycholinguistics (Dingemanse, 2015; Dingemanse and Enfield, 2015; Dingemanse and Floyd, 2014; Dingemanse et al, 2014; Enfield, 2013). This eclectic approach to the analysis of Alto Perené conversational data gives this presentation an advantage of situating the microanalysis of the turns at talk of a less-studied language in the rich cultural context of native speakers’ ways of living.…”
Section: Methodsmentioning
confidence: 99%